Transplantation of human dental pulp stem cells promotes peripheral nerve regeneration after sciatic nerve injury in rats - Seong, Kyung-Joo; Kim, Won-Jae; Chung, Hyun-Woo; Oh, Hee-Kyun; Park, Hong-Ju; Jung, Ji-Yeon (International journal of oral biology, 2024)
Mesenchymal stem cells (MSCs) have emerged as a promising therapeutic resource for the peripheral nervous system (PNS) and central nervous system (CNS) that is attributable to their capacity for neuronal differentiation. Human dental pulp stem cells (hDPSCs), which exhibit MSC-like traits, can differentiate into neuron-like cells and secrete critical neurotrophic factors; however, their therapeutic potential in peripheral nerve injury remains unexplored. This study investigated the regenerative effects of hDPSC transplantation following sciatic nerve injury (SNI) in rats. Transplantation of hDPSCs, STRO-1+ hDPSCs, or CD146+ hDPSCs after sciatic nerve transection in rats upregulated the levels of β3 tubulin, a marker of immature newborn neurons. Furthermore, the levels of glial cellderived neurotrophic factor, insulin-like growth factor 2, and the neuroregenerative factor NeuroD1 were upregulated. Motor dysfunction in rats with SNI was restored, as demonstrated by significantly higher sciatic functional index scores compared with the sciatic nerve transection group without transplantation. Transplantation of hDPSCs into injured peripheral nerves results in the upregulation of neurotrophic factors, differentiation into immature neurons, and promotion of motor function recovery. This approach holds promise as a valuable therapeutic strategy for repairing injured peripheral sciatic nerves, potentially providing a solution for nerve damage in both the PNS and CNS.